4 - Les associations en milieu urbain dakarois : classification et capacités développantes: 10.4314/ad.v25i1.22111 - Niang, Abdoulaye (Africa Development, 2000)
In Senegal, urban associations are extremely evolutionary in concept and practice and pervade every aspect of urban space. They shift and adjust, in both their forms and objectives, to the social and institutional demands of their ever-changing environment, as well as to the new opportunities provided by same. Urban associations in Senegal offer solutions that increasingly meet individual and collective needs, which makes them appear as efficient local development tools, especially when members and communities strongly identify themselves with their native homeland.